ANALISIS KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA SEKTOR INDUSTRI KONSUMSI PERIODE 2000-2010 - Taofiqkurochman, Cecep; Konadi, Win (JURNAL KEBANGSAAN, 2012)
Dividend policy is one of the company function to reach the increasing of company value. Company should determine dividend policy in a good way because with it company can decide how many percent from company profit would be shared to the stock holders until the company target to increase prosperous of stockholders can be full filled. The purpose of this research is to know how far the dividend policy variable which are liquidity, profitability, risk, financing, investment and ownership to stock price company which are unite in consumers goods industry period 2000-2010. Sample that used are 25 companies. Research method used to reach that point is description method or systematically visual of fact, characteristic or relationship inter phenomenon from the matter that is investigated then test hypothesis or variable relationship from statistic calculation by analyzed verivicative using Path Analysis method. Simultaneously test result show that variable dividend policy which are only risk factor and Financing significantly influence to stock price.